Actualization Of The Teachings Of The Samin Indigenous People In The Indonesian Government - Hasan, Ahmad Muwafi Nur; Bashori, Imam Ali (AL-ADYAN, 2023)
Indonesia is a country that has hundreds of indigenous peoples scattered throughout the archipelago, who still survive with their customs and traditions. One of them is the samin indigenous people from Dukuh Karangpace, Klopoduwur Village, Blora Regency, Central Java. The indigenous Samin people were described as ignorant, unwilling to pay taxes, and refused forced labor by the Dutch colonists. The Samin traditional community is considered strange and also considered to reject technological advances. There are several problems in Indonesian society, especially Indonesian government officials. Such as public lying, corruption, illegal levies, bribes, legal mafia cases involving law enforcement officials, and state officials in making decisions that only benefit certain groups, and so on. From this problem, this paper will use an indigenous religion paradigm approach and local wisdom to see the true nature of Samin's teachings. the author uses a type of library research that is included in qualitative research. The result of the interim conclusion of this paper is that the author argues that the teachings of samin are very relevant if applied to society in general and the government in particular, there are three main points of Samin teachings including the understanding of the Samin indigenous people with the creator, living environment and people, so it can be concluded that the negative stigma of the assumption to the Samin indigenous people is considered inappropriate and the samin teachings are very relevant if actualized as a reference in Indonesian society and government. Keywords: Samin indigenous people, Government, Indigenous religion paradigm.AbstrakIndonesia adalah negara yang memiliki ratusan masyarakat adat yang tersebar di seluruh nusantara, yang masih bertahan dengan adat dan tradisinya. Salah satunya adalah masyarakat adat samin dari Dukuh Karangpace, Desa Klopoduwur, Kabupaten Blora, Jawa Tengah. Orang asli Samin digambarkan sebagai orang yang cuek, tidak mau membayar pajak, dan menolak kerja paksa oleh penjajah Belanda. Masyarakat adat Samin dianggap aneh dan juga dianggap menolak kemajuan teknologi. Ada beberapa masalah dalam masyarakat Indonesia, khususnya pejabat pemerintah Indonesia. Seperti pembohongan publik, korupsi, pungutan liar, suap, kasus mafia hukum yang melibatkan aparat penegak hukum, dan penyelenggara negara dalam pengambilan keputusan yang hanya menguntungkan kelompok tertentu, dan sebagainya. Dari permasalahan tersebut, tulisan ini akan menggunakan pendekatan paradigma agama leluhur dan kearifan lokal untuk melihat hakikat ajaran Samin. penulis menggunakan jenis penelitian kepustakaan yang termasuk dalam penelitian kualitatif. Hasil kesimpulan sementara dari tulisan ini adalah penulis berpendapat bahwa ajaran samin sangat relevan jika diterapkan pada masyarakat pada umumnya dan pemerintah pada khususnya, ada tiga pokok utama ajaran samin diantaranya adalah pengertian masyarakat adat samin dengan pencipta, lingkungan hidup dan manusia, sehingga dapat disimpulkan bahwa stigma negatif anggapan terhadap masyarakat adat Samin dianggap kurang tepat dan ajaran samin sangat relevan jika diaktualisasikan sebagai acuan dalam masyarakat dan pemerintahan Indonesia.Kata kunci: Masyarakat adat Samin, Pemerintah, Paradigma agama adat.